2010
DOI: 10.7326/0003-4819-153-7-201010050-00008
|View full text |Cite
|
Sign up to set email alerts
|

Age at Cancer Diagnosis Among Persons With AIDS in the United States

Abstract: Background Studies have reported young ages at cancer diagnosis in HIV-infected people, suggesting that HIV accelerates carcinogenesis. However, these comparisons did not account for differences in population age structures. Objective To compare ages at diagnosis for non-AIDS-defining cancers arising in the AIDS and general populations, after adjusting for differences between these populations in age and other demographic characteristics. Design Registry linkage study Setting 15 U.S. HIV/AIDS and cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
148
3
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(165 citation statements)
references
References 35 publications
8
148
3
4
Order By: Relevance
“…43 In contrast, a registry linkage study showed that the age of CRC was no different in groups infected with HIV and the general population. 3 The USPSTF recommends CRC screening with intervals between screening studies depending on the modality used for cancer detection (Table 2). 44 These include high-sensitivity fecal occult blood testing (FOBT) annually, sigmoidoscopy every 5 years with FOBT every 3 years, or colonoscopy every 10 years in adults who are deemed at average risk for CRC beginning at age of 50 years and continuing until age of 75 years.…”
Section: Colorectal Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…43 In contrast, a registry linkage study showed that the age of CRC was no different in groups infected with HIV and the general population. 3 The USPSTF recommends CRC screening with intervals between screening studies depending on the modality used for cancer detection (Table 2). 44 These include high-sensitivity fecal occult blood testing (FOBT) annually, sigmoidoscopy every 5 years with FOBT every 3 years, or colonoscopy every 10 years in adults who are deemed at average risk for CRC beginning at age of 50 years and continuing until age of 75 years.…”
Section: Colorectal Cancermentioning
confidence: 99%
“…2 Non-ADM in PLWHA are often typified by earlier age at onset, more aggressive clinical course and more advanced stage at presentation. 3,4 For many of these tumors, such as lung cancer and other aero-digestive tumors, the occurrence of cancer is linked to lifestyle choices, including tobacco use and alcohol consumption. 5 Co-infection with other viruses including hepatitis B virus (HBV), hepatitis C virus (HCV), and human papillomavirus (HPV) results in additive risks for liver cancer and squamous neoplasms of the head and neck, anus, and cervix.…”
mentioning
confidence: 99%
“…29 Some cancers (mainly anal cancer, liver cancer and Hodgkin's lymphoma) occur at younger ages in those infected with HIV compared to those without HIV. 30 Osteoporosis and fragility-related fractures occur more often in HIV-infected persons.…”
Section: Hiv-associated Non-aids Complications (Hana)mentioning
confidence: 99%
“…17 Since then, a number of studies carried out either exclusively before the HAART era or both before and during the HAART era have suggested that lung cancer risk is greater among HIV-infected individuals compared to the general population (Table 1). 11,12,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] Though some of the largest studies included only patients with an AIDS-defining diagnosis 11,18,21,22 several cohort and registry linkage studies, which have included HIV-positive patients with and without AIDS, have also consistently demonstrated an increased risk of lung cancer. 19,23,27,[28][29][30]33 In a meta-analysis of seven reports of HIV-associated cancer risk and published between 2002 and 2006, 444,172 people with HIV/AIDS were identified, of whom 1,297 were diagnosed with lung cancer.…”
Section: Epidemiologymentioning
confidence: 99%
“…40,[52][53][54][55][56][57][58][59][60][61][62] Yet, in a recent registry linkage study, the difference in the age at diagnosis of lung cancer was relatively modest between persons with AIDS and the general population (50 vs. 54 years) after adjusting for the underlying population structures. 31 In HIV-infected patients with lung cancer, men are significantly overrepresented compared to women, with a male-female sex ratio of 5-10:1. This likely reflects the epidemiology of lung cancer, as well as HIV/AIDS; in developing countries, both diseases affect men disproportionately compared to women.…”
Section: Clinical Characteristicsmentioning
confidence: 99%